Fiscal policy in an estimated open-economy model for the Euro area - Ratto, Marco; Roeger, Werner; Veld, Jan in't 1962-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper uses an estimated DSGE model for the euro area to study the effects of fiscal stabilisation policies. There are at least two features of the euro area economy which makes this analysis interesting. First, there are nominal rigidities in goods and labour markets, and there are financial market frictions with a significant share of liquidity constrained households. Second, the government is a major sector of the euro area economy. In this paper we look at fiscal stabilisation via government consumption, investment, transfers and wage taxes. Empirical evidence is found for systematic countercyclical fiscal policy. Consistent with previous findings, there is a small positive fiscal multiplier in the case of transitory fiscal shocks. It is found that fiscal policy is effective in stabilising GDP in the presence of demand and supply shocks. Fiscal policy helps to reduce the demand externality arising from nominal rigidities. In addition automatic stabilisation via government transfers helps to smooth consumption of liquidity constrained household. Fiscal policy partly compensates the financial market distortion. With distorted goods, labour and financial markets it is found that the estimated fiscal policy rules reduce fluctuations in euro area GDP by about 14 percent.
Economic Papers